Yogurt: Effect on leukocytes and blood coagulation in an acute liver injury model - Haro, Ana Cecilia (2009)
This study determined whether cow or goat yogurt administration has a preventive effect on the hepatic damage undergone during an acute liver injury. Acute liver injury was induced by an intraperitoneal injection of d-galactosamine. Groups of mice were fed with cow or goat yogurt for 2 days or 7 days before the d-galactosamine injection. Blood and liver samples were obtained 12 hours after d-galactosamine inoculation. d-Galactosamine induced an increase in serum aminotransaminases, a reduction in the number of blood leukocytes, an enhancement in neutrophil myeloperoxidase activity, a recruitment of leukocytes toward the liver, an increase in cell death, and an alteration in prothrombin time, activated partial thromboplastin time, and fibrinogen levels. Treatment with cow or goat yogurt was effective at increasing leukocyte number and decrease myeloperoxidase activity. We also observed a decrease in leukocyte accumulation in the liver and a reduction in cell death. Activated partial thromboplastin time and fibrinogen were normalized, but prothrombin time only showed an improvement without reaching normal values. Cow or goat yogurts were effective at protecting against an experimental acute liver injury, especially when administered for 7 days.